Variations in the financial impact of the COVID-19 pandemic across 5 continents: a cross-sectional, individual level analysis - Khetan, AK; Yusuf, S; Lopez-Jaramillo, P; Szuba, A; Orlandini, A; Mat-Nasir, N; Oguz, A; Gupta, R; Avezum, Á; Rosnah, I; Poirier, P; Teo, KK; et al. (Elsevier, 2022)
Background COVID-19 has caused profound socio-economic changes worldwide. However, internationally comparative data regarding the financial impact on individuals is sparse. Therefore, we conducted a survey of the financial impact of the pandemic on individuals, using an international cohort that has been well-characterized prior to the pandemic.